Implementasi Protokol LoRa pada Akuisisi Data Sensor Perikanan menggunakan Drone Agent sebagai Node Perantara - Ammar Waliyuddin Jannah; Rakhmadhany Primananda; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Smart aquaculture is one of the aquaculture concepts that applies the concept of the Internet of Things (IoT) in monitoring water quality remotely. The components used are sensor nodes, gateways, and clouds. These three components play a role in sending and retrieving water quality data using the LoRa and MQTT communication protocols. LoRa communication is used to send and receive data between the sensor node and the gateway, while communication to connect the gateway to the cloud uses the MQTT protocol. Water quality monitoring has been studied before but still has limitations in certain conditions, where the sensor node and the cloud do not have a direct connection. Then the data transmission from the research cannot be done so an agent as an intermediary sensor node is needed for the cloud. One agent that can be used as an intermediary sensor node to the cloud is the drone. The drone agent is used as a gateway to connect the sensor node and the cloud. There are two tests conducted, namely functional testing and performance testing. In functional testing, sensor nodes that have been implemented successfully retrieve data using temperature, pH, dissolved oxygen, and turbididty sensors. Performance testing is carried out to determine the ability of the system when sending sensor data to the drone agent. Performance testing is measured by sending delay and success ratio parameters with 1hop distance scenario. The results of the 1hop distance scenario test with a drone flight height of 10m from the ground, at 100m distance variation gets an average delivery delay of 523.53 ms with a success ratio of 100%, at 300m distance variation gets a mean shipping delay of 747.43 ms with a success ratio of 100%, at a variation of distance 600m has an average delivery delay of 541.70 ms with a success ratio of 90%.